Combined effect of a probiotic (Bifidobacterium) and a prebiotic (polydextrose) on the fecal microbiota and stool parameters of healthy young women. Issue 5 (2017) - Aoe, Seiichiro; Nakazawa, Yuta; Ohmisya, Shinji
No abstract available